Integrasi Teknologi dalam Pembelajaran PAI Untuk Meningkatkan Kualitas Pembelajaran di Sdn 1 Kecila - Yazid Abdul Qadir Jawaz Mr; Muh. Hanif (Tarbiatuna: Journal of Islamic Education Studies, 2024)
ABSTRACT This research explores the integration of technology in Islamic Education (Pendidikan Agama Islam) learning at SDN 1 Kecila. In the digital era, the use of technology in education has become a necessity, including at the elementary level. This integration has the potential to enhance the effectiveness and efficiency of learning by improving concept comprehension, student engagement, and digital skill development. The study aims to identify strategies, benefits, and challenges of technology integration in Islamic Education as well as its practical implications. Constructivist theory suggests that technology can enrich students' interactions with learning materials, while competency-based learning and cooperative learning theories emphasize the development of students' abilities through feedback and collaboration. The results of this study (Odden, 1991, hlm. 76)are expected to provide insights for educational decision-makers in improving the quality of Islamic Education learning in elementary schools. Technology integration is expected to enhance learning quality, student engagement, and material accessibility, as well as support the balanced development of students' spiritual, social, and intellectual competencies. ABSTRAK Penelitian ini mengeksplorasi integrasi teknologi dalam pembelajaran Pendidikan Agama Islam di SDN 1 Kecila. Di era digital, penggunaan teknologi dalam pendidikan telah menjadi suatu kebutuhan, termasuk di tingkat sekolah dasar. Integrasi ini berpotensi meningkatkan efektivitas dan efisiensi pembelajaran dengan memperbaiki pemahaman konsep, keterlibatan siswa, dan pengembangan keterampilan digital. Penelitian ini bertujuan untuk mengidentifikasi strategi, manfaat, dan tantangan integrasi teknologi dalam Pendidikan Agama Islam serta implikasi praktisnya. Teori konstruktivis menunjukkan bahwa teknologi dapat memperkaya interaksi siswa dengan materi pembelajaran, sementara teori pembelajaran berbasis kompetensi dan pembelajaran kooperatif menekankan pengembangan kemampuan siswa melalui umpan balik dan kolaborasi. Hasil dari penelitian ini diharapkan dapat memberikan wawasan bagi para pembuat keputusan pendidikan dalam meningkatkan kualitas pembelajaran Pendidikan Agama Islam di sekolah dasar. Integrasi teknologi diharapkan dapat meningkatkan kualitas pembelajaran, keterlibatan siswa, dan aksesibilitas materi, serta mendukung pengembangan seimbang kompetensi spiritual, sosial, dan intelektual siswa. Keyword: Technology Integration, Islamic Education, Elementary Education, Constructivism, Competency-Based Learning